The integrated deterministic model for a vendor manage inventory in a two-stage supply chain - Abdul Rahim, Mohd Kamarul Irwan; S.R. Nadarajan, Santhirasegaran; Razalli, Mohd Rizal (Penerbit UTM Press, 2015)
In a two-stage supply chain system, vendor managed inventory (VMI) policies is an integrating decisions between a supplier and his retailers.The supplier assumes the responsibility of maintaining inventory at its retailers and ensuring that they will not run out of stock at any moment.This paper discusses an optimization approach, considering the model of static demand on the inbound as well as the outbound inventory for a two-stage supply chain implementing VMI. In the proposed solutions for coordinating the single warehouse multiple-retailers (SWMR) system, retailers are first clustered to minimize the within-cluster travel costs and distances and are then replenished using an optimal direct shipping strategy satisfying some additional restrictions